Identifying Great Street in Bandung as Part of Bandung Technopolis Concept: a Perception-Based Approach - Dessy Syarlianti (Institut Teknologi Sepuluh Nopember, 2017)
Great Street is required for making a great city. Bandung will develop new City Centre Service (CCS) in Gede Bage with Bandung Technopolis concept which one of the main programs is making Bandung Great Street. It is important to see potencies and problems based on the user perspective so that the concepts will be applicative and effective. Using the perception-based approach, this paper aims to identify the perception of the street user in Bandung based on their experience in using the streets in Bandung, so it can lead to a contextual concept. From Jacobs’s Great Street Criteria, the PPS’s criteria and Bandung Great Street criteria can be summarized into five normative variables such as activities, comfortable and amenities, walkability and transportation option, visual attractiveness, and local identity. The analyzed variables are preferences of the favorite street in Bandung, the reasons, the real usages of the street, the way of using the street, the companion in using the street, and the interesting things. These variables represent all normative variables which combined with three perception variables such as cognitive, affective and conative. After analyzing the data, it can be concluded that the respondents prefer Ir. H. Djuanda Street, Braga Street, and RE Martadinata Street as the most favorite street, and choose Cihampelas Street as the least favorite street